Chemoprevention of Human Actinic Keratoses by Topical dl-α-Tocopherol - Foote, Janet A. (2009)
Prior research shows that topical application of free, non-fatty acid conjugated vitamin E (dl-α-tocopherol) prevents skin cancer in mice, as well as immunosuppression induced by UVB radiation (Nutr. Cancer 26, 183–191, 1996). This study investigated the chemopreventive potential of dl-α-tocopherol in humans through monitoring surrogate endpoint biomarkers in sun-damaged skin. METHODS: Contralateral arms of healthy human volunteers with actinic keratoses (AKs) were randomly assigned to receive either 12.5% dl-α-tocopherol or placebo in a crème base for 6 months. Changes in number of AKs, levels of p53 protein expression, proliferating cell nuclear antigen (PCNA) and polyamines were assessed along with skin and systemic vitamin E levels. RESULTS: Following treatment, plasma concentration levels of dl-α-tocopherol were unchanged, but skin levels were highly elevated (p<0.001). Levels of p53 and PCNA did not change significantly while number of AKs declined insignificantly in both placebo and treatment arms. Regression models demonstrated significant decreases in putrescine, spermidine, spermine, and total polyamine concentrations following treatment. DISCUSSION: Topically applied dl-α-tocopherol was substantially absorbed in skin, but the 6-month application did not significantly reduce numbers of pre-existing AKs on moderately to severely sun-damaged forearms. Increases in polyamine synthesis are expected during tumor initiation and promotion; conversely, the significant reductions in polyamine levels resulting from the topical dl-α-tocopherol application are consistent with reductions in tumorigenesis potential. Topical tocopherol did not normalize established sun-induced lesions, but dl-α-tocopherol induced reductions in polyamine metabolism are consistent with the inhibition of skin squamous cell carcinogenesis as seen in previous human trials and animal models.